Cataract Surgery in Patients with Keratoconus: Pearls and Pitfalls - Aiello, F. (Open Ophthalmol J, 2017)
BACKGROUND: Keratoconus (KC) is a common ectatic disorder resulting in progressive corneal thinning and irregular astigmatism. It has been observed that patients affected by KC are more likely to develop lens opacities earlier compared to non-keratoconic patients. OBJECTIVE: Intraocular lens (IOL) selection and refractive outcome prediction are among a number of factors that can make cataract surgery in keratoconic patients challenging. Accurate biometry is often difficult to obtain due to unreliable K measurements and lack of dedicated biometric formulae. The use of toric IOLs has also been investigated. CONCLUSIONS: Determining the stage of KC, pre-operative patient counselling and the preferred method of refractive correction are all crucial to obtain successful postoperative outcomes and good patient satisfaction. The use of toric IOLs can achieve good results only in selected low-grade keratoconic eyes.